The state and prospects for the development of the accounting and information system in Ukraine - Zadorozhnyi, Zenovii-Mykhailo; Muravskyi, Volodymyr; Ometsinska, Iryna (Herald of Economics, 2025)
Analytical Report Based on the Results of the VII International Scientific and Practical Conference "Current State and Prospects for the Development of the Accounting and Information System in Ukraine" (Ternopil, West Ukrainian National University, September 26–27, 2024)